GAMBARAN SPIRITUALITAS ORANG DALAM PENGAWASAN (ODP) COVID-19 YANG MENGALAMI ANXIETY: SEBUAH STUDI FENOMENOLOGIS - K Kasmi; M Maemonah; N Nurjannah (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2021)
Society that is troubled by the COVID-19 outbreak that has swept the world today has a profound influence on people's lives, not least for students who have to undergo a period of quarantine and experience high anxiety which impacts on their spirituality. This study aims to determine the forms of spirituality of students with ODP status and currently undergoing quarantine in overcoming anxiety experienced by these students. This research uses a qualitative research method of phenomenology type. The results showed that the spiritual forms experienced by the ODP undergoing quarantine were trusting in God by increasing compulsory worship and sunah, searching for meaning, mindfulness by carrying out ha breathing, remembrance, and reading the Qur'an, and feeling safe because of undergoing the educational quarantine process. Other than, Forms of spiritual communication carried out by the subject are thaharah, syahadat, shalat, tawakkal, thanksgiving, patience, and repentance.